2018
DOI: 10.1039/c8nr06182c
|View full text |Cite
|
Sign up to set email alerts
|

A self-encapsulated porous Sb–C nanocomposite anode with excellent Na-ion storage performance

Abstract: In this study, a self-encapsulated Sb–C nanocomposite as an anode material for sodium-ion batteries (SIBs) was successfully synthesised using an SbCl3–citrate complex precursor, followed by a drying and calcination process under an inert N2 atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The strong attachment would benefit the charge transfer between SbPO 4 and the BC x matrix and retain the integrity of the electrode upon cycling, thereby improving the cycling stability and rate capability. 14,15,25 The XRD patterns in Fig. 3d To examine the crystallinity of the BC x matrix, Raman spectra of the SbPO 4 /BC x , Sb/BC x and Sb/C samples are recorded (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong attachment would benefit the charge transfer between SbPO 4 and the BC x matrix and retain the integrity of the electrode upon cycling, thereby improving the cycling stability and rate capability. 14,15,25 The XRD patterns in Fig. 3d To examine the crystallinity of the BC x matrix, Raman spectra of the SbPO 4 /BC x , Sb/BC x and Sb/C samples are recorded (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…36 This porous structure inhibits the volume expansion of the electrode upon cycling by providing sufficient vacant sites and enables better ion transport through the electrolyte to the active material. 25 The electrochemical performance of the SbPO 4 /BC x hybrid anode for SIBs was evaluated by cyclic voltammetry (CV), galvanostatic discharge-charge cycling, and electrochemical impedance spectroscopy (EIS). Fig.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…As a result, the O element was frequently detected for the synthesized cabonaceous materials. [2,13] This indicated that, in the present work, the surface of C present in the Sb/C-600 composite was functionalized during the synthesis process.…”
Section: Resultsmentioning
confidence: 66%
“…The complete covering of the C layer ensured the good electrical contact among the Sb active material particles. [13] Remarkably, the presence of O element was still detected although the sample was deaerated under high vaccum condition prior to TEM-EDS measurement, and the Sb2O3 phase in the Sb/C-600 composite was no longer detected by XRD. According to the previous report, [7] the presence of O element in the Sb/C-600 sample possibly results from its highly porous structure, which easily adsorbed oxygen from the air on the surface of the material.…”
Section: Resultsmentioning
confidence: 98%
“…As exhibited in Figure 4h, in comparison with the previously reported Sb-based full cell, the rate capability of the Na 3 V 2 (PO 4 ) 3 @C/Sb 2 O 3 @RGO is comparable. [28][29][30] For the full cell based on the total mass of the anode and cathode materials, a practical energy density of 152.1 Wh Kg −1 and power density of 975.4 W Kg −1 was achieved. Furthermore, although with increasing current density, the outputted medium voltage has no obvious decrease, suggesting good rate capability (Supporting Information Figure S27).…”
Section: Resultsmentioning
confidence: 99%